Developing and validation of COVID-19 media literacy scale among students during the COVID-19 pandemic - Hanieh Jormand; Majid Barati; Saeed Bashirian; Salman Khazaei; Ensiyeh Jenabi; Sepideh Zareian (BMC Psychology, 2023)
Abstract Objective This cross-sectional validation work evaluated the psychometric features of the COVID-19 Media Literacy Scale (C-19MLs) in Students. Methods The study was conducted on 530 students from a medical university in Hamadan, Iran, who were recruited through a stratified cluster random sampling process in June-July 2020. Intraclass Correlation Coefficient (ICC) and internal consistency were used to assess the reliability. Moreover, CFA (Confirmatory Factor Analyses) and EFA (Exploratory Factor Analyses) were carried out to examine construction validity. CVR (Content Validity Ratio) and CVI (Content Validity Index) were used to examine the content validity. Results According to the factor analysis, it was indicated that the C-19MLs included 21 items measuring five dimensions (constructedness of credible Covid-19 media messages, contractedness of fake media coronavirus messages, fake media coronavirus messages, audience, with three questions in each factor; format, represented lifestyles in fake media coronavirus messages with six questions in each factor) for an explanation of 58.4% of the prevalent variance. The average scores for the CVI and CVR were respectively 0.94 and 0.77. According to confirmatory factor analysis, the studied model had an appropriate fitting to the data; the relative chi-square (x2/df) = 2.706 < 3, RMSEA = 0.093 ≤ 0.1; CFI = 0.893 ≥ 0.9; TLI = 0.874 ≥ 0.9; GFI = 0.816 ≥ 0.9; and SRMR = 0.06 ≤ 0.08. Further analyses represented acceptable findings for internal consistency reliability values with 0.86 of Cronbach’s alpha. Conclusions The results proved that the C-19MLs is a reliable and valid tool, and it is suitable and acceptable now and can be utilized in forthcoming investigations. This highlights educators and stakeholders to realize the importance of participating individuals in the new media ecology and new ‘Infomedia’ ecosystems for enabling people in the current digital society.